Analysis of priority locations for the development of Fishery Ports in the Southern of Java Island - Lia Kusumawati; Arief Sudianto; Suharyanto Suharyanto (Sekolah Tinggi Ilmu Pertanian Wuna, 2023)
Fishing port has a strategic role to encourage the development of the fishing industry and generate a regional economy. In the spatial plan, a fishing port is one of the forms of spatial structures, and the zoning plan has a Fishing Port Zone for the working and operation of the fishing port area. The aim of this study is to determine the priority fishing ports in the South of Java Island which will be developed and accommodated in the zoning plan and spatial plan policies within the framework of regional development. The method used in this study is to perform weighting and scoring analysis on criteria and sub-criteria based on the physical aspects, disaster, accessibility, spatial planning and space utilization, fishery, and prospect estimation. The result of this study concludes that the priority fishing port locations that can be further developed, namely: PPN Prigi, PPS Cilacap, and PPN Palabuhan Ratu.